Pharmacoeconomic aspects of the targeted drugs use in psoriatic arthritis in context of the Russian healthcare system - O. I. Ivakhnenko; T. V. Korotaeva; T. V. Dubinina; A. M. Lila (Современная ревматология, 2022)
Objective: to study the clinical and economic aspects of the use of biological disease modifying antirheumatic drugs (bDMARDs) and targeted synthetic DMARDs (tsDMARDs), Janus kinase inhibitors (JAKi), for the treatment of psoriatic arthritis (PsA).Patients and methods. The study included adult patients (age ≥18) with active PsA, bionaive or previously treated with bDMARDs. Comparison technologies included: adalimumab (ADA), guselcumab, golimumab, ixekizumab, secukinumab (SEC), tofacitinib (TOFA), certolizumab pegol (CZP), upadacitinib (UPA), ustekinumab, etanercept. The efficacy and safety of the bDMARDs and tsDMARDs included in the study were evaluated based on the results of a systematic search and analysis of data on the comparative clinical efficacy and safety of their use. First of all, the results of phase III randomized controlled trials of drugs that are used to treat active PsA in adult patients as active treatment compared with placebo or with another active drug, or systematic reviews with meta-analysis (MA) and network MA based on them, were considered. The period from the 12th to the 24th week after the start of therapy was taken as the time point for assessing the clinical efficacy of drugs, and the frequency of achieving the ACR20/50/70 criteria was taken as the performance indicator. Cost per responder (СpR), calculated on the basis of the cost of PsA therapy by the time a response is achieved according to the ACR20/50/70 criteria, was used as a criterion for clinical and economic efficiency and to analyze the impact on the budget.Results and discussion. The data of the performed MA indicate a significantly greater effectiveness of the analyzed bDMARDs and JAKi compared to placebo in terms of the frequency of achieving a response according to the ACR20/50/70 criteria both in the group of bionaive patients and in the group of PsA patients, previously treated with bDMARDs. There were no differences between the drugs included in the study in terms of the frequency of achieving ACR20/50/70 response during the treatment of PsA. According to the study, by the 24th week of therapy, ADA, UPA and SEC 150 mg were characterized by the lowest costs to achieve the ACR20/50/70 criteria in bionaive patients and ACR20/50 in patients who were previously treated with bDMARDs. A low CpR value was determined in cases of ADA 40 mg and UPA 15 mg use for the treatment of patients with PsA who had not previously received bDMARDs. Among interleukin inhibitors, the lowest CpR value was registered for SEC 150 mg. By the 12th week of treatment, the CpR of TOFA 5 mg was higher compared to that of UPA 15 mg. CpR indicators for achieving ACR20/50 criteria in patients who were previously treated with bDMARDs were lower in UPA 15 mg and CZP compared to other drugs.Conclusion. The results of the study demonstrate the clinical and economic feasibility of introducing different bDMARDs and JAKi into real practice of PsA treatment. At the same time, the use of original drugs is not always associated with significant costs per 1 patient who responded to treatment. In the absence of direct comparisons, real clinical practice provides important information about the relative efficacy and safety of alternative therapies in the management of PsA patients.